Peran Arus Kas Bebas dalam Menurunkan Praktik Manajemen Laba: Studi pada Industri Perbankan Indonesia - Fayliencent, Ignatz Novrian; Christin Meirdhika Lekatompessy (CV.ITTC INDONESIA, 2025)
This study aims to analyze the effect of free cash flow on earnings management practices in banking companies listed on the Indonesia Stock Exchange (IDX) from 2017 to 2023. The research method used is quantitative with a descriptive approach and multiple regression analysis. Free cash flow is measured as the difference between operating cash flow and investing cash flow divided by total assets, while earnings management is measured using the Modified Jones Model through discretionary accruals. The results show that free cash flow has a negative and significant effect on earnings management. This finding indicates that the higher a company's free cash flow, the less likely it is to engage in earnings management practices. This reflects that strong free cash flow can be a positive signal to stakeholders, reduce the need for accounting manipulation, and strengthen transparency and trust in a company's financial statements. This research contributes to investors, management, and regulators in understanding the role of free cash flow strategy in financial decision-making and corporate governance